Safety and efficacy evaluation of christia vespertilionis extracts on breast cancer cell lines - Zakaria, Muhammad Asyaari (Pusat Pengajian Sains Perubatan, 2018)
Breast cancer is one of the common malignancies among women worldwide. There is a constant demand for new therapies to treat this complex disease. Notably, scientific research is drawing its attention towards medicinal plants as a potential source for anticancer agents. Christia vespertilionis is a local herb claimed to have anticancer properties. It is widely marketed as a food supplement in Malaysia thus raise an awareness regarding their efficacy and safety. Moreover, current research about the mechanisms of its anticancer potential is also limited. Herein, this study aimed to evaluate the efficacy of C. vespertilionis extracts on breast cancer cell lines (MDAMB- 231 and MCF-7) and to investigate the mode of cell death that underlies its anticancer effects. Besides, the phytochemical in CVME and heavy metals of the plant were also investigated. The cytotoxic activities of CVME, CVAE and tamoxifen was evaluated by MTT assay while the mode of cell death was evaluated by Annexin VFITC and PI staining. The phytochemical and heavy metal analysis were investigated by GC-MS and ICP-MS, respectively. Results from MTT assay showed that CVME significantly inhibits proliferation of MDA-MB-231 cells line (p<0.05) and the effect was selectively cytotoxic towards cancerous cells only. Furthermore, this study showed that CVME induces apoptosis as indicated by a significant increase of apoptotic cell percentage (p<0.05) when compared with untreated cells. CVME was also found to contain numbers of pharmacologically bioactive compounds that possess anticancer activities such as phytol and 10-undecenoic acid. Hazardous heavy metal analysis revealed that this plant contains a high concentration of chromium which may cause toxic side effects. Overall, this study demonstrates the potential applications of C. vespertilionis as an anticancer drug for breast cancer treatment.